Cardiovascular Risk Factors and Total Serum Antioxidant Capacity in Healthy Men and in Men with Coronary Heart Disease. (11th August 2014) - Gawron-Skarbek, Anna; Chrzczanowicz, Jacek; Kostka, Joanna; Nowak, Dariusz; Drygas, Wojciech; Jegier, Anna; Kostka, Tomasz
Abstract : Whether the incidence of coronary heart disease (CHD) is related to a decrease in total antioxidant capacity (TAC) has not yet been completely clarified. We assessed TAC of blood serum in a group of 163 men with CHD aged 34.8–77.0 years and in 163 age-matched peers without CHD. Two spectrophotometric methods were applied to assess TAC: ferric reducing ability of serum (TAC-FRAS) and 2.2-diphenyl-1-picryl-hydrazyl (TAC-DPPH) tests. In the CHD group, multivariate analysis revealed that uric acid (UA), triglycerides, and systolic blood pressure contributed independently to the TAC-FRAS variance. TAC-DPPH was favorably predicted by UA concentration, but negatively so by current smoking and glucose levels. In men without CHD, UA was the only independent determinant of both TAC-FRAS and TAC-DPPH. Presence of CHD was not an independent predictor of TAC—observed between-group differences (higher TAC in CHD patients) disappeared after adjustment for other confounders. We conclude that UA is the main determinant of TAC of blood serum in men. TAC is not directly influenced by age or CHD but is related to several indices of overweight/obesity and laboratory measures of metabolic syndrome, especially in patients with CHD.